Religione Ragione e LIBERTÀ. Presentazione del libro di Massimo Fagioli Roma, 17 ottobre 2014 - Fagioli, Massimo (Il sogno della farfalla, 2015)
On 17th October 2014 the book Religione Ragione e LIBERTÀ (Religion Reason and FREEDOM), a collection of the lessons Massimo Fagioli held in 2009 at the University of Chieti-Pescara “G. D’Annunzio”, was presented at the Feltrinelli Bookshop in Rome. As well as the author, psychiatrists and psychotherapists Matteo Madrucci, Tiziana Amici and Elena Pappagallo spoke during the presentation. The lessons deal with topics that range from the history of psychiatry to the Author’s own research into human reality involving a radical refusal of religious ideologies and rationalism in order to give rise to a psychiatry which must be a medicine of the mind offering a treatment and a cure. The talks pick up on some of the main arguments contained in the book linking them to more recent developments in the work of the Collective Analysis and in Fagioli’s research.